Fouling behavior of isolated dissolved organic fractions from seawater in reverse osmosis (RO) desalination process - Yin, Wenqiang (2021)
Organic fouling is still elusive in seawater reverse osmosis (SWRO) desalination process. Classifying organics in seawater will provide an in-depth understanding of the important fraction on RO fouling. In this study, dissolved organic matter (DOM) in seawater was fractionated and concentrated by membrane technique into three major fractions (i.e., biopolymer fraction, humic substance with building block fraction, and low molecular weight fraction) by their molecular weight (MW) according to the definitions in liquid chromatography with organic carbon detection (LC-OCD) method. Overall recovery of >80% was attained. The isolated organic fractions were compared with common model foulants such as sodium alginate (SA), bovine serum albumin (BSA), and humic acid (HA), in terms of chemical analyses using fluorescence-excitation emission matrix (FEEM) and LC-OCD, as well as their fouling potentials. SWRO fouling experiments were carried out and fouling mechanism was investigated by atomic force microscopy (AFM) method and extended Derjaguin-Landau-Verwey-Overbeek (XDLVO) theory. Results showed that initial fouling (i.e., foulant-membrane interaction) was the main driver in SWRO organic fouling with biopolymer fraction as the major contributor followed by low molecular weight fraction. In addition, divalent ions was found to enhance the RO fouling by increasing the adhesion and cohesion forces between foulant-membrane and foulant-foulant.